Hereditary Neuropathy with Liability to Pressure Palsies - Hyoung Won Choi; Nancy L. Kuntz (Pediatric Neurology Briefs Publishers, 2015)
Investigators from 4 pediatric hospitals in Canada analyzed the clinical presentation and electrophysiological data of 12 children with hereditary neuropathy with liability to pressure palsies (HNPP), caused by PMP22 gene deletion.